Genetic Diversity and Differentiation of MHC Class I Genes in Red-Crowned Crane Populations - Xu, Nan; Ye, Wentao; Sun, Chenghe; He, Ke; Zhu, Ying; Lan, Hong; Lu, Changhu; Liu, Hongyi (Frontiers in Ecology and Evolution, 2022)
The red-crowned crane (Grus japonensis) has been demoted to “vulnerable species” because its populations have apparently stabilized in Japan and Korea. Low variation and genetic drift may cause damage to the nascent recovery of the G. japonensis population. The major histocompatibility complex (MHC) is one of the most polymorphic gene families in the vertebrate genome and can reflect information on the adaptive evolution of endangered species. In this study, variations in MHC I exon 3 of captive G. japonensis in China were assessed and compared with those in cranes from Japan. Forty MHC alleles of 274 base pairs were isolated from 32 individuals from two captive populations in China. There was high variability in the nucleotide and amino acid composition, showing the proportion of polymorphic sites of 18.98% and 32.97%, respectively. Comparative analyses of the Chinese and Japanese populations based on 222 base pair sequences revealed more alleles and higher variation in the Chinese population. The lack of significant geographical differentiation of G. japonensis was supported by the genetic differentiation coefficient (0.04506) between the Chinese and Japanese populations. Positive selection of antigen-binding sites was observed, which contributed to maintaining the diversity of MHC class I genes. Phylogenetic analysis suggested the persistence of trans-species polymorphisms among MHC class I genes in Gruidae species. Our results may contribute to optimizing the management of G. japonensis populations and population recovery of this threatened species.